PEMBERDAYAAN MASYARAKAT MELALUI PROGRAM GELAR PRODUK UNGGULAN DESA DALAM MEMBANGUN KEMANDIRIAN MASYARAKAT - Novia Rizky; Rani Nuraeni; Nur Ainun Najmi; Abdul Latif Mubarok; Zahra Syifa Rozan (Jurnal Pengabdian Masyarakat Indonesia, 2023)
Community empowerment is a development process in which people take the initiative to start a process of social activities to improve their own situation and condition. The title of village flagship products is a forum to promote and introduce village superior products to the community, business people, financiers, and is expected to attract investors. The Village flagship Product Title was attended by 27 villages from 258 villages representing each sub-district in Ciamis Regency. This event will be held for two days, namely on October 11 and 12, 2022. This research uses descriptive methods and is analyzed in a qualitative way. Data collection is carried out in 3 ways, interviews, observation and documentation. Research techniques using participatory observation techniques. The results of the study can be concluded that the Village Flagship Product Title program and counseling on the benefits of digital marketing are able to build village independence: Each village government can create at least one village superior product, Village superior products from each village can be known by the wider community, Able to utilize technology to market digitally, Able to create branding for the products owned.